The Bilirubinemia - Delgado Febres, Ernesto (1949)
Bilirubin was studied in 201 aduyltos and apparently healthy subjects (159 men and 42 women), which is the largest number that has been given on this matter. It also has been studied a grupoi of subjects, as one apparent abnormality with high numbers of indirect bilirubin excretion rate and test for this pigment (in all cases where they studied) inadequate; condition which, under different names, has been studied by several authors, whose knowledge has great value. Has also been studied serum bilirubin and liver function related to the excretion of this pigment in different conditions of anoxemia; chronic, acute (exposure for 4 hours and 7 days); and also from both points of view a group of native subjects of Morocoha transferred to Lima, in order to observe the behavior of bilirubin from the blood was studied, and the corresponding liver function when done cease anoxemia. In pathological conditions has made ​​a comparative study and in some cases serial 144 sick, the data provided by the technique Malloy and Evelyn, are the classic reaction of Van den Bergh is supplied.